Robot Assisted Laser Osteotomy - Burgner, Jessica (KIT Scientific Publishing, 2010)
In the scope of this thesis world's first robot system was developed, which facilitates osteotomy using laser in arbitrary geometries with an overall accuracy below 0.5mm. Methods of computer and robot assisted surgery were reconsidered and composed to a workflow. Adequate calibration and registration methods are proposed. Further a methodology for transferring geometrically defined cutting trajectories into pulse sequences and optimized execution plans is developed.